Pengaruh Pemahaman Bertransaksi, Kemudahan, Dan Manfaat Dalam Menggunakan Webform BSI Terhadap Kepuasan Nasabah Di BSI - Salma Hasna Nafis; Inka Clarina Melyana (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2023)
With changes in Bank Syariah Indonesia digital transaction, the mindeset of customers and bank employees needs to be changed to improve themselves in using digital banking facilities, so learning about this requires understanding, convenience, and the benefits of using digital banking in order to create satisfaction in use. This study aims to determine the understanding, convenience, and benefits of using the Webform BSI on customer satisfaction at BSI. This research uses quantitative research method and uses IBM SPSS version 26 as a test tool to assist data processing and data collection. This study uses a sample of FEBI IAIN Kudus 2020-2022 students who have savings at BSI by using an accidental sampling technique, namely a sampling technique where anyone who meets the resercher by chance and can be used as a sample, people who happen to be found are suitable as data source. The results of this study indicate that understanding of transactions using the Webform BSI partically affects customer satisfaction. The ease of using the Webform BSI partically does not affect customer satisfaction. The benefits of using the Webform BSI partically affect customer satisfaction.